Development of Website Service Governance at the Muhammadiyah University Palembang Using the ITIL V3 Method - Kemas Muhammad, Wahyu Hidayat; Widya, Cholil; Tri Basuki, Kurniawan (INTI International University, 2022)
The problems in implementing an integrated information technology-based service are the need for data standards, the readiness of the system in sharing data, the availability of the system, the large usage load, and the reluctance of users to take advantage of the existing website system at the University of Muhammadiyah Palembang in utilizing an integrated website system. The research will propose an ITIL (Information Technology Infrastructure Library) framework to review service practices in IT Service Management from an integrated service system used in tertiary institutions and use the ITIL V3 Service Design and Service Operation framework. The results of this study are in the form of service processes that must be prioritized to solve problems, as well as based on the value of service management processes that must and need to be improved.